Lifestyle and reproductive health: effects of diet and glyphosate exposure on fertility, feto-placental development and uterine carcinogenesis - Gastiazoro, María Paula (2023)
Fil: Gastiazoro, María Paula. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas; Argentina.